The Influence Of Country Image And Destination Image On Intention To Visit South Korea - NURHAYAT, Kartika; SHIRATINA, Aldina (PT Keberlanjutan Strategis Indonesia, 2021)
The purpose of this study is to examine and analyze the influence of country image, destination image and destination familiarity on visit intentions to South Korea with destination familiarity as a moderating variable. The data used in this study is the result of a questionnaire that was distributed directly in March 2021. Sampling was carried out through a purposive sampling method, where the researcher had set several criteria. There are 150 respondents in this study. This research method uses PLS-SEM with the help of SMART PLS. The results in this study indicate that country image, destination image and destination familiarity has a positive significant influence on intention to visit, as well as the moderating relationship between destination image and country image on intention to visit The managerial implications suggest where innovations need to be improved that are more attractive and take advantage of the great potential of South Korea's image. For further research, researchers are advised to look at the Visit more broadly so that they can better observe and explore the problems that exist in South Korea